The Influence of Empathy and Morality of Violent Video Game Characters on Gamers’ Aggression - Gao, Xuemei; Weng, Lei; Zhou, Yuhong; Yu, Hongling (Frontiers in Psychology, 2017)
According to the General Aggression Model, situational factors (such as the game characters) and personal factors both affect a gamer’s acquisition of aggressive behavior. Previous studies have found not only that the surface features of game characters, such as appearance and clothing, but also that their inherent characteristics, such as morality and identity, can influence a gamer’s attitude and behavior. Research has also shown that empathy, as a personal factor, can protect gamers from the impact of media violence. However, past research has focused primarily on single factors affecting the player rather than more comprehensive investigations. This study investigates the influence of the game character’s moral features and levels of empathy on the gamer’s aggression. The participants were 120 Chinese university students (61 females and 59 males) with ages ranging from 17 to 27 years. Participants first completed a series of questionnaires: a user experience questionnaire, a video game questionnaire, the Buss-Perry Aggression Questionnaire, and a modified version of the Interpersonal Reactivity Index. All participants then had 5min of practice playing a violent video game. They were then divided into three groups: a high empathy group, a low empathy group, and a no empathy group. After the practice, participants in the high and low empathy groups read empathy materials relating to the game characters; participants in the no empathy group began formal gameplay. All participants played the game for 20min. Finally, participants were required to complete the Scale of Hostility Status questionnaire, the Implicit Aggression Test, and the Competitive Reaction Time Test. The results show that empathy and the morality of game characters both influence aggression, but empathy affected aggression differently in the participants playing justified roles (i.e., killing others fora moral reason in the game) compared to those playing unjustified roles (i.e., killing others for immoral reasons in the game). In the high empathy condition, the implicit aggression of justified players was significantly higher than those playing unjustified roles. However, high empathy does not always play a protective role, and its effect is restricted by the features of the game characters.